Fuzzy AHP for drought risk assessment in Lam Ta Kong watershed, the north-eastern region of Thailand - Saowanee WIJITKOSUM (Soil and Water Research, 2018)
Droughts occur from a combination of natural factors and human activities rather than just a single natural cause. Spatial factors have also heavily influenced the causes of draught. This study was conducted in the Lam Ta Kong watershed, Thailand. In this study, the Fuzzy Analytic Hierarchy Process (FAHP) method was applied to evaluate the risk of agricultural drought and the GIS technique was employed to give full consideration to the ambiguity and uncertainty of the agricultural drought risk. There are five risk factors to consider in the agricultural drought risk assessment and they are divided in a total of fifteen criteria: physical factors (slope gradient and elevation), climatic (rainfall and aridity index), soil (texture, drainage, fertility, erosion, and soil salinity), land utilization (land use and land cover) and water resources (precipitation days, stream density, distance from an irrigation canal, and groundwater volume). These criteria determine the weight and score used to evaluate their parental risk factors. The Analytic Hierarchy Process (AHP) was applied together with the triangular fuzzy numbers (TFNs) method to assess the data obtained from the criteria to achieve the drought risk assessment. The results indicated that the overall risk of the Lam Ta Kong area was at a moderate risk of agricultural drought (50.45%), of which 15.63% of the total area was at a high risk of agricultural drought. Moreover, 0.40% of the total area located at the central part of the watershed was at a very high risk which was due to its saline soil with > 50% dense salt crust. This research indicated that the major factors causing droughts in the watershed were related to the soil factors, especially soil texture, soil fertility and soil salinity. These soil factors were considered as the driving factors of drought. The results of this study can be used for land use planning and water resource management in order to prepare for droughts in the watershed.